A catalyst for catalytic ozonation of organic pollutants and a preparation method and application thereof

CN122912853APending Publication Date: 2026-10-16TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610939518.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

本发明制备得到的催化剂具有高臭氧催化活性,不仅能够催化臭氧降解难降解有机污染物阿特拉津,在30min内能够去除95.4%的阿特拉津,反应速率常数达到0.111min-1;还可用于磺胺甲噁唑、卡马西平、环丙沙星、布洛芬和苯酚的臭氧降解,可在6min内实现卡马西平的完全降解、3min内实现磺胺甲噁唑和环丙沙星的完全降解,具有非常高的臭氧催化活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912853A_ABST
    Figure CN122912853A_ABST
Patent Text Reader

Abstract

The application discloses a catalyst for catalyzing ozone to degrade organic pollutants and a preparation method and application thereof, and belongs to the technical field of organic pollutant treatment. The application mixes a mixed solution of citrate and a water-soluble active metal salt with a potassium ferricyanide solution, and then is placed at room temperature to form a Prussian blue analogue. The Prussian blue analogue is calcined under an argon atmosphere to obtain a catalyst with a core-shell structure, wherein the shell layer is a carbon layer, and the inner core is an active metal-iron alloy. The catalyst has high catalytic activity and high stability, can catalyze ozone to degrade the refractory organic pollutant atrazine, and the removal rate of atrazine is only reduced by 5.5% after 5 cycles of oxidative degradation. The catalyst also has high catalytic activity for sulfamethoxazole, carbamazepine and ciprofloxacin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ozone degradation of organic pollutants, and particularly to a catalyst for catalyzing the degradation of organic pollutants by ozone, its preparation method, and its application. Background Technology

[0002] With rapid economic and technological development, water resources have suffered from varying degrees of pollution, among which the accumulation of recalcitrant organic pollutants (ROCs) has become increasingly prominent. ROCs are discharged into the aquatic environment through domestic sewage, medical wastewater, industrial wastewater, and agricultural wastewater. Due to their persistence, bioaccumulation, and potential ecotoxicity, large-scale discharge of these organic pollutants poses a serious threat to human health and the ecological environment. However, traditional water treatment technologies are inefficient, costly to operate, and prone to generating toxic and harmful intermediate byproducts, making it difficult to achieve efficient removal of ROCs.

[0003] Advanced oxidation processes (AOPs) primarily work by generating highly reactive free radicals (such as hydroxyl radicals •OH and superoxide radicals •O). 2- Ozone (O3) oxidation technology, which uses O3 as an oxidant to degrade and mineralize recalcitrant organic pollutants, has shown great application potential in the field of water treatment. Ozone (O3) oxidation technology, in particular, uses O3 as an oxidant to oxidize and degrade organic pollutants in water. It is commonly used for decolorization, deodorization, water disinfection, and pollutant degradation, and has advantages such as being economical, efficient, environmentally friendly, and easy to operate. However, ozone treatment alone still faces several technical bottlenecks, such as the slow rate of O3 decomposition to produce •OH, and the presence of matrix components in the water (such as CO3). 2- SO4 2- NO3 - The rapid removal of •OH by O3 molecules (such as OH-) limits the overall oxidation efficiency of the indirect oxidation process. Simultaneously, the low solubility and stability of O3 molecules in water significantly reduce O3 utilization. Therefore, direct oxidation of organic pollutants by O3 molecules is difficult to achieve efficiently.

[0004] Compared to homogeneous O3 oxidation technology, heterogeneous O3 catalytic oxidation technology mainly uses synthesized solid catalysts to catalytically decompose O3 molecules, thereby generating highly oxidizing reactive species (surface atomic oxygen, singlet oxygen (1O2), •OH, •O). 2-Ozone oxidation (O3) is a process that degrades pollutants in water. For heterogeneous O3 catalysis, the composition, morphology, size, and active sites of the catalyst significantly affect its catalytic performance. Subtle adjustments to the parameters and details of the catalyst preparation method can have a major impact on these properties, thus affecting ozone catalytic activity. Currently, common catalysts include metal oxides, metal-supported composite catalysts, and carbon materials. However, metal-based catalysts exhibit strong chemical activity, and ozone has a stronger oxidizing power than other oxidants such as peracetic acid. This makes metal-based catalysts more prone to chemical changes during O3 catalysis, leading to insufficient catalytic activity and reduced stability. Most metal catalysts experience a decrease in catalytic activity of at least 8% after multiple cycles of ozone degradation. Therefore, controlling the composition, morphology, size, and active sites of metal-based catalysts through the details of their preparation to construct an ozone catalyst with both high activity and high stability has become a core requirement for advancing metal-based catalyst-catalyzed ozone oxidation technology. Summary of the Invention

[0005] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, the object of the present invention is to provide a solution.

[0006] To achieve the above objectives, the first aspect of the present invention provides a method for preparing a catalyst for catalytic ozone degradation of organic pollutants, comprising the following steps: S1. Mix the mixed solution of citrate and water-soluble active metal salt with potassium ferricyanide solution to obtain the precursor solution; S2. The precursor solution is allowed to stand at room temperature to form a Prussian blue analogue, thus obtaining the precursor. S3. The precursor is calcined under an argon atmosphere to obtain the catalyst; The water-soluble active metal salt includes at least one of water-soluble cobalt salt or water-soluble nickel salt.

[0007] The preparation method of the present invention, through the series process design of co-precipitation and high-temperature calcination in an inert atmosphere, can controllably construct the precursor structure and achieve efficient carbon coating, enhance the synergistic effect of the interface, and the process of the present invention is mild and controllable, simple to operate, mild conditions, and readily available raw materials, making it suitable for large-scale production.

[0008] In the preparation processes of steps S1 and S2, water-soluble cobalt salts or water-soluble nickel salts are used to provide divalent metal ions, and ferricyanide provides [Fe(CN)6]. n-The cyano ligand, divalent metal ions, and iron ions are attracted to each other by electrostatic attraction. The divalent metal ion coordinates with the nitrogen-terminus of the cyano group, while the iron ion remains coordinated with the carbon-terminus of the cyano group. Self-assembly is gradually completed through cyano bridging (Co-N≡C-Fe). At the same time, the introduction of citrate slows down the coordination reaction rate and inhibits excessively rapid nucleation and crystallization, ultimately yielding a highly crystalline, cubic Prussian blue analogue.

[0009] In the high-temperature calcination process under argon atmosphere in step S3, the Prussian blue analog precursor undergoes structural collapse under high-temperature conditions, and the organic ligand cyano is derived into an ultrathin carbon layer. The two metals are transformed into an alloy to form an inner layer. The formation of the core-shell structure can not only improve the intercontact between the carbon layer and the metal inner layer and promote the regulation of electronic structure, but also promote the decomposition and activation of O3 by electron transfer between the carbon layer and the metal. It can also inhibit metal leaching in the aqueous environment and improve the stability of the catalyst.

[0010] The precursor preparation process of this invention mainly involves simple mixing, precipitation, and aging of metal salts to obtain a large quantity of the target material. The entire preparation process is simple and easy to operate, with readily available raw materials and controllable costs. The reaction conditions are not harsh, facilitating industrial-scale production and solving the problem of complex preparation processes and difficulties in large-scale application of novel catalysts.

[0011] The catalyst obtained by the method of this invention can significantly promote O3 activation and •O 2- / 1 The generation of O2 improves the utilization rate of O3 and exhibits high efficiency in removing recalcitrant organic pollutants under different pH values, different water quality substrates and anion interference. It also has good cycle stability, providing a new solution for heterogeneous O3 catalytic treatment of recalcitrant organic wastewater.

[0012] According to some embodiments of the present invention, in step S1, the molar ratio of the water-soluble active metal salt to the potassium ferricyanide is 5-7:3-5, preferably 3:2.

[0013] According to some embodiments of the present invention, in step S1, the concentration of the water-soluble active metal salt in the mixed solution is 25-35 mmol / L, preferably 30 mmol / L.

[0014] According to some embodiments of the present invention, in step S1, the water-soluble cobalt salt is cobalt nitrate and the water-soluble nickel salt is nickel nitrate.

[0015] According to some embodiments of the present invention, in step S1, the concentration of potassium ferricyanide in the potassium ferricyanide solution is 15-25 mmol / L, preferably 20 mmol / L.

[0016] According to some embodiments of the present invention, in step S1, the molar ratio of the water-soluble active metal salt to the citrate is 1:1.3-1.8, preferably 1:1.5.

[0017] According to some embodiments of the present invention, in step S1, the concentration of citrate in the mixed solution is 10-15 g / L, preferably 13 g / L.

[0018] According to some embodiments of the present invention, in step S1, the citrate is sodium citrate.

[0019] According to some embodiments of the present invention, in step S1, the mixed solution is mixed with the potassium ferricyanide solution by stirring for 2-5 minutes.

[0020] According to some embodiments of the present invention, in step S2, the settling time is 20-25 h, preferably 24 h, to ensure that the precipitation reaction proceeds fully.

[0021] According to some embodiments of the present invention, in step S2, the heating and calcination method includes: heating to 650-750°C at a rate of 3-8°C / min and maintaining it for 2-5 hours.

[0022] According to some embodiments of the present invention, in step S2, the heating and calcination method may be: heating to 700°C at a rate of 5°C / min and maintaining for 2 hours to complete the carbonization of the Prussian blue analogue.

[0023] According to a second aspect of the invention, a catalyst prepared by the above-described preparation method is also provided.

[0024] Specifically, the catalyst has a core-shell structure, wherein the shell layer is a carbon layer and the core is an active metal-iron alloy, the shell layer covers the surface of the core, and the active metal-iron alloy is a cobalt-iron alloy or a nickel-iron alloy.

[0025] The catalyst of this invention exhibits significantly enhanced catalytic activity, structural stability, and interference resistance.

[0026] The improvement in catalytic activity mainly relies on the metal Co (Co 0 / Co 2+ / Co 3+ ) and Fe (Fe 0 / Fe 2+ / Fe 3+ The interaction between the O3 and the ultrathin carbon shell accelerates electron transfer, promoting O3 decomposition and thus continuously generating •OH and •O. 2- , 1This catalyst utilizes multiple highly reactive oxygen species, including O2, to enhance the removal efficiency of organic pollutants. Compared to carbon-coated monometallic catalysts and O3 oxidation technology alone, this catalyst can achieve a removal rate of over 90% for recalcitrant organic pollutants such as atrazine, significantly improving O3 catalytic activity.

[0027] Furthermore, the catalyst of this invention has a core-shell structure, with an active metal-iron alloy coated inside a carbon layer. This carbon coating not only increases the contact area between the carbon layer and the active metal-iron alloy, promoting electron transfer between them, but also prevents external environmental corrosion of the active metal-iron alloy, significantly reducing the risk of metal ion dissolution. Experimental verification shows that this catalyst maintains high catalytic activity even after multiple cycles, overcoming the poor structural stability of existing metal-based catalysts and reducing replacement costs in practical applications.

[0028] Furthermore, the catalyst of this invention, through the interaction between the active metal-iron alloy and the carbon layer, enables the catalyst to withstand water quality fluctuations (such as different pH values) and anion interference (such as CO3). 2- Cl - Under various conditions, it maintains high catalytic activity. Furthermore, it maintains high catalytic activity under different water matrix conditions (Dasha River water, campus lake water, and tap water).

[0029] According to some embodiments of the present invention, the thickness of the shell layer is 2~20 nm.

[0030] According to some embodiments of the present invention, the diameter of the core is 100~300nm.

[0031] According to some embodiments of the present invention, the catalyst contains 25% to 30% iron and 35% to 40% active metal.

[0032] According to some embodiments of the present invention, the valence states of iron in the catalyst include zero, divalent, and trivalent, and the valence states of cobalt include zero, divalent, and trivalent.

[0033] According to a third aspect of the invention, the above-described catalyst is provided for use in the catalytic degradation of organic pollutants by ozone.

[0034] According to a fourth aspect of the present invention, a method for ozone degradation of organic pollutants in water is provided, comprising the following steps: The catalyst was added to the water sample to be treated, and ozone was introduced to carry out the oxidation reaction.

[0035] According to some embodiments of the present invention, the concentration of the organic pollutant is 10-100 mg / L, specifically any value among 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, and 100 mg / L, such as 15 mg / L, or any range formed by both, such as 10 mg / L to 50 mg / L.

[0036] According to some embodiments of the present invention, the dosage of the catalyst is 0.1-1 g / L, specifically any value among 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L, and 1 g / L, such as 0.25 g / L, or any range formed by both, such as 0.1 g / L to 0.5 g / L.

[0037] According to some embodiments of the present invention, the concentration of the introduced ozone is 10-30 mg / L, specifically any value among 10 mg / L, 12 mg / L, 15 mg / L, 18 mg / L, 20 mg / L, 22 mg / L, 25 mg / L, 28 mg / L, and 30 mg / L, such as 20 mg / L, or any range formed by both, such as 10 mg / L to 25 mg / L.

[0038] According to some embodiments of the present invention, the flow rate of the introduced ozone is 0.1-0.5 L / min, specifically any value among 0.1 L / min, 0.2 L / min, 0.3 L / min, 0.4 L / min, and 0.5 L / min, such as 0.1 L / min, or any range formed by both, such as 0.1 L / min to 0.3 L / min.

[0039] According to some embodiments of the present invention, the oxidation reaction is carried out at a temperature of 25°C and for a time of 10-60 min, specifically any value among 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, and 60 min, such as 30 min, or any range formed by both, such as 10 min to 50 min.

[0040] According to some embodiments of the present invention, the organic pollutant includes at least one of atrazine, ibuprofen, ciprofloxacin, sulfamethoxazole, carbamazepine, or phenol.

[0041] According to some embodiments of the present invention, the water sample includes, but is not limited to, tap water, lake water, or river water.

[0042] According to some embodiments of the present invention, the water sample contains NO3. - Cl - CO3 2- HCO3 - or HPO4 - At least one of them.

[0043] According to some embodiments of the present invention, the pH of the water sample is 3 to 9.

[0044] The degradation method of the present invention has high degradation efficiency, can completely remove recalcitrant organic pollutants, has a wide range of applications, strong anti-interference ability, low operating cost, simple operation and environmental protection, fast degradation rate and short treatment cycle.

[0045] The beneficial effects of this invention are: The catalyst prepared by this invention exhibits high ozone catalytic activity, capable of catalyzing the ozone degradation of the recalcitrant organic pollutant atrazine, removing 95.4% of atrazine within 30 minutes, with a reaction rate constant of 0.111 min. -1 It can also be used for the ozone degradation of sulfamethoxazole, carbamazepine, ciprofloxacin, ibuprofen and phenol. It can achieve complete degradation of carbamazepine within 6 minutes and complete degradation of sulfamethoxazole and ciprofloxacin within 3 minutes, and has very high ozone catalytic activity.

[0046] The catalyst prepared in this invention exhibits high ozone catalytic stability; after five cycles of catalytic ozone degradation of atrazine, the atrazine removal rate decreased by only 5.5%, and the NO3 removal rate was significantly lower. - Cl - CO3 2- HCO3 - HPO4 - It maintains high catalytic activity even in the presence of impurity ions and is suitable for pH conditions of 3 to 9. Attached Figure Description

[0047] Figure 1 This is a microscopic morphology diagram of the catalyst in Example 1 of the present invention.

[0048] Figure 2 This is the XPS spectrum of the catalyst in Example 1 of this invention.

[0049] Figure 3 This is a degradation efficiency diagram of the catalyst in Example 1 and the comparative example of the present invention.

[0050] Figure 4 This is a graph showing the degradation efficiency of the catalyst in Example 1 of the present invention under different water quality conditions.

[0051] Figure 5This is a graph showing the degradation efficiency of the catalyst in Example 1 of the present invention for different organic pollutants.

[0052] Figure 6 This is a diagram showing the recycling efficiency of the catalyst in Example 1 of the present invention. Detailed Implementation

[0053] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0054] In the description of this invention, the terms "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0055] Unless otherwise specified, "room temperature" in this invention means 25℃±5℃.

[0056] Unless otherwise specified, "about" in this invention means that the allowable error is within ±2%.

[0057] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0058] Example 1 Example 1 describes the preparation of a water treatment ozone catalyst, the specific process of which is as follows: Step S1: Add 2 mmol of K3[Fe(CN)6] to 100 mL of ultrapure water to obtain solution A. Add 3 mmol of Co(NO3)2•6H2O and 1.3 g of sodium citrate dihydrate (C6H9Na3O9) to 100 mL of ultrapure water to obtain solution B. Slowly add solution A to solution B to obtain a mixed solution. Step S2: The mixed solution was stirred continuously for 2 min, then allowed to stand at room temperature for 24 h, and then dried by centrifugation to obtain a cobalt iron Prussian blue analogue; Step S3: The cobalt-iron Prussian blue analogue was heated to 700°C at a rate of 5°C / min and held for 2 h under an argon atmosphere to complete the carbonization treatment, and finally carbon-coated cobalt-iron alloy catalyst (CoFePBA-700) was obtained.

[0059] Example 2 Example 2 prepared a water treatment ozone catalyst, the specific process of which is as follows: Step S1: Add 2 mmol of K3[Fe(CN)6] to 100 mL of ultrapure water to obtain solution A. Add 3 mmol of Ni(NO3)2•6H2O and 1.3 g of sodium citrate dihydrate (C6H9Na3O9) to 100 mL of ultrapure water to obtain solution B. Slowly add solution A to solution B to obtain a mixed solution. Step S2: The mixed solution was stirred continuously for 2 min, then allowed to stand at room temperature for 24 h, and then dried by centrifugation to obtain a nickel-iron Prussian blue analogue; Step S3: The nickel-iron Prussian blue analogue was heated to 700°C at a rate of 5°C / min and held for 2 h under an argon atmosphere to complete the carbonization treatment, and finally carbon-coated nickel-iron alloy catalyst (NiFePBA-700) was obtained.

[0060] Comparative Example 1 Comparative Example 1 prepared a carbon-coated cobalt metal ozone catalyst, the specific process of which is as follows: Step S1: Add 2 mmol of K3[Co(CN)6] to 100 mL of ultrapure water to obtain solution A. Add 3 mmol of Co(NO3)2•6H2O and 1.3 g of sodium citrate dihydrate (C6H9Na3O9) to 100 mL of ultrapure water to obtain solution B. Slowly add solution A to solution B to obtain a mixed solution. Step S2: The mixed solution was stirred continuously for 2 min, then allowed to stand at room temperature for 24 h, and then dried by centrifugation to obtain a cobalt iron Prussian blue analogue; Step S3: The cobalt-iron Prussian blue analogue was heated to 700°C at a rate of 5°C / min and held for 2 h under an argon atmosphere to complete the carbonization treatment, and finally carbon-coated cobalt-iron alloy catalyst (CoPBA-700) was obtained.

[0061] Comparative Example 2 Comparative Example 2 prepared a carbon-coated metallic iron ozone catalyst, the specific process of which is as follows: Step S1: Add 2 mmol of K3[Fe(CN)6] to a mixed solution of 100 mL of ultrapure water and ethanol to form solution A (the volume ratio of water to ethanol is 3:1). Add 3 mmol of Fe(NO3)3•9H2O and 1.3 g of C6H9Na3O9 to 100 mL of ultrapure water to obtain solution B. Slowly add solution A to solution B to obtain a mixed solution. Step S2: The mixed solution is stirred continuously for 2 min, then allowed to stand at 80°C for 24 h, and then dried by centrifugation to obtain a cobalt iron Prussian blue analogue; Step S3: The cobalt-iron Prussian blue analogue was heated to 700°C at a rate of 5°C / min and held for 2 h under an argon atmosphere to complete the carbonization treatment, and finally carbon-coated cobalt-iron alloy catalyst (CoFePBA-700) was obtained.

[0062] Comparative Example 3 Comparative Example 3 prepared a carbon-coated cobalt-iron ozone catalyst, the specific process of which is as follows: Step S1: Add 2 mmol of K3[Fe(CN)6] to 100 mL of ultrapure water to obtain solution A. Add 3 mmol of Co(NO3)2•6H2O and 1.3 g of sodium citrate dihydrate (C6H9Na3O9) to 100 mL of ultrapure water to obtain solution B. Slowly add solution A to solution B to obtain a mixed solution. Step S2: The mixed solution was stirred continuously for 2 min, then allowed to stand at room temperature for 24 h, and then dried by centrifugation to obtain a cobalt iron Prussian blue analogue; Step S3: The cobalt-iron Prussian blue analogue is heated to 700°C at a rate of 5°C / min and held for 2 h under a nitrogen atmosphere to complete the carbonization treatment, and finally carbon-coated cobalt-iron alloy catalyst is obtained.

[0063] Comparative Example 4 Comparative Example 4 prepared a carbon-coated cobalt-iron ozone catalyst, the specific process of which is as follows: Step S1: Add 2.5 mmol of K3[Fe(CN)6] to 50 mL of ultrapure water to obtain solution A. Add 2.5 mmol of CoCl2 and 1.5 g of polyvinylpyrrolidone (PVP) to 100 mL of ultrapure water to obtain solution B. Slowly add solution A to solution B to obtain a mixed solution. Step S2: The mixed solution was stirred continuously for 4 h, then allowed to stand at room temperature for 20 h, and then dried by centrifugation to obtain a cobalt iron Prussian blue analogue; Step S3: The cobalt-iron Prussian blue analogue is heated to 600°C at a rate of 5°C / min and held for 2 h under an argon atmosphere to complete the carbonization treatment, and finally carbon-coated cobalt-iron alloy catalyst is obtained.

[0064] Comparative Example 5 Comparative Example 5 prepared a carbon-coated cobalt-iron ozone catalyst, the specific process of which is as follows: Step S1: Add 0.2 g of K3[Fe(CN)6] and 0.3 g of Co(CH3COO)2·4H2O to 60 mL of ultrapure water to obtain solution A. Add 0.44 g of sodium citrate dihydrate (C6H9Na3O9) and 3 g of polyvinylpyrrolidone to 40 mL of ultrapure water to obtain solution B. Slowly add solution A to solution B to obtain a mixed solution. Step S2: The mixed solution is continuously stirred for 2 min, then aged at 80°C for 12 h, and then centrifuged and dried to obtain a cobalt iron Prussian blue analogue; Step S3: The cobalt-iron Prussian blue analogue is heated to 700°C at a rate of 5°C / min and held for 2 h under an argon atmosphere to complete the carbonization treatment, and finally carbon-coated cobalt-iron alloy catalyst is obtained.

[0065] Characteristic 1 SEM and TEM images of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 are shown in [the original text]. Figure 1 .

[0066] Figure 1 The SEM images show that CoPBA-700, FePBA-700, and CoFePBA-700 all exhibit irregular nanoparticle morphologies. TEM results confirm that the catalysts of CoPBA-700, FePBA-700, and CoFePBA-700 all possess a core-shell structure, with an outer ultrathin carbon layer and cores of Co, Fe, and CoFe alloy, respectively, proving that the synthesized catalysts have a core-shell structure. Furthermore, the high-resolution TEM image of CoFePBA-700 shows a lattice spacing of 0.2 nm, corresponding to the (110) crystal plane of the CoFe alloy. EDS elemental images confirm the presence of C, N, O, Fe, and Co elements in the CoFePBA-700 catalyst, further confirming the formation of CoFePBA-700.

[0067] Characteristic 2 XPS plots of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 are shown in [reference needed]. Figure 2 .

[0068] Figure 2The high-resolution XPS spectrum of C confirms the presence of C-C, CN, and CO bonds. The characteristic peaks in the high-resolution XPS spectrum of Co confirm that the valence state of the Co species is Co. 0 Co 2+ and Co 3+ The presence of characteristic peaks in the high-resolution XPS spectrum of Fe confirms that the valence state of the Fe species is Fe. 0 Fe 2+ and Fe 3+ Coexistence. Compared to CoPBA-700 and FePBA-700, the binding energy of CoFePBA-700 is shifted, proving that there is electron transfer between carbon and cobalt-iron metal.

[0069] Characteristic 3 The content of each element in the catalyst prepared in Example 1 was determined by ICP, and the content of cobalt was 37.52% and the content of iron was 26.09%.

[0070] Performance Test 1 Atrazine (ATZ), a widely used triazine herbicide, remains in surface and groundwater year-round due to its high stability and biodegradability, posing a threat to ecosystems and human health. Traditional water treatment processes struggle to effectively remove this type of pollutant.

[0071] The catalysts from Examples 1 and 1-2 were mixed with ATZ-containing wastewater and subjected to catalytic ozone oxidation under ozone conditions to degrade ATZ. The concentration of ATZ in the wastewater was 15 mg / L, the dosage of each catalyst in the wastewater was 0.25 g / L, the wastewater volume was 0.2 L, the temperature was 25°C, the time was 30 min, and the ozone concentration generated by the ozone generator was 20 mg / L, which was introduced into the wastewater at an ozone flow rate of 0.1 L / min.

[0072] See processing results Figure 3 The ATZ removal rate of each catalyst and k obs Ozone (SO) treatment alone only achieved a 53.4% ​​removal rate of ATZ, indicating limited catalytic effect. Adding monometallic catalysts CoPBA-700 and FePBA-700 significantly improved the removal rate (86.4% and 83.4%, respectively), demonstrating a synergistic effect between the monometallic catalyst and the carbon layer. Compared to monometallic catalysts, the introduction of CoFePBA-700 further enhanced the ATZ removal rate, achieving 95.4% removal within 30 minutes, with a reaction rate constant of 0.111 min. -1 It is superior to ozone alone (0.025 min). -1 CoPBA-700 (0.073 min) -1) and FePBA-700 (0.064 min -1 ).

[0073] Performance Test 2 To investigate the degradation performance of the catalyst of this invention on ATZ under different pH conditions, ozone degradation experiments on ATZ were conducted under the following conditions: The catalyst from Example 1 was mixed with ATZ-containing wastewater at pH 3, pH 7, and pH 9, respectively, and subjected to catalytic ozone oxidation under ozone conditions to complete the degradation of ATZ. The concentration of ATZ in the wastewater was 15 mg / L, the dosage of the catalyst in the wastewater was 0.25 g / L, the wastewater volume was 0.2 L, the temperature was 25°C, the time was 30 min, and the ozone concentration generated by the ozone generator was 20 mg / L, which was introduced into the wastewater at an ozone flow rate of 0.1 L / min.

[0074] Figure 4 Figure 'a' illustrates the effect of the catalyst of Example 1 on the degradation performance of ATZ under different pH conditions (pH 3-9). The results show that the catalyst has good water quality adaptability and exhibits high catalytic efficiency in catalytic ozone degradation treatment under different pH conditions, indicating that the catalyst has good practical application.

[0075] Performance Test 3 To investigate the degradation performance of the catalyst of this invention on ATZ under different types of aqueous substrates, ozone degradation experiments on ATZ were conducted under the following conditions: The catalyst from Example 1 was mixed with ATZ-containing wastewater samples from tap water, lake water, and river water, respectively. Catalytic ozone oxidation was then carried out under ozone conditions to degrade ATZ. The concentration of ATZ in the wastewater was 15 mg / L, the catalyst dosage was 0.25 g / L, the wastewater volume was 0.2 L, the temperature was 25°C, the time was 30 min, and the ozone generator produced an ozone concentration of 20 mg / L, which was introduced into the wastewater at an ozone flow rate of 0.1 L / min.

[0076] Figure 4 Figure b illustrates the effect of the catalyst of Example 1 on the degradation performance of ATZ under different types of water matrix conditions (tap water, lake water, and river water). The results show that the catalyst has good water quality adaptability and exhibits high catalytic efficiency in catalytic ozone degradation treatment under different types of water matrix conditions, indicating that the catalyst has good practical application.

[0077] Performance Test 4 To investigate the degradation performance of the catalyst of this invention on ATZ under different anion interferences, ozone degradation experiments on ATZ were conducted under the following conditions: The catalyst of Example 1 was reacted with NO3-containing substances. - Cl - CO3 2- HCO3 - HPO4 - Wastewater containing ATZ was mixed and subjected to catalytic ozone oxidation under ozone conditions to degrade ATZ. The concentration of ATZ in the wastewater was 15 mg / L, the dosage of the catalyst was 0.25 g / L, the concentration of anions in the wastewater was 12 mmol / L, the wastewater volume was 0.2 L, the temperature was 25℃, the time was 30 min, and the ozone concentration generated by the ozone generator was 20 mg / L, which was introduced into the wastewater at an ozone flow rate of 0.1 L / min.

[0078] Figure 4 Figure c illustrates the effect of the catalyst of Example 1 on the ATZ degradation performance under different anion interference conditions, used to comprehensively evaluate its practical applicability. The results show that the catalyst has good water quality adaptability and exhibits high catalytic efficiency in catalytic ozone degradation treatment under different anion interference conditions, indicating that the catalyst has good practical applicability.

[0079] Performance Test 5 To investigate the degradation performance of the catalyst of this invention on different organic pollutants, ozone degradation experiments were conducted under the following conditions: The catalyst from Example 1 was mixed with wastewater containing sulfamethoxazole, carbamazepine, ciprofloxacin, ibuprofen, and phenol, respectively, and subjected to catalytic ozone oxidation under ozone conditions to degrade the aforementioned organic pollutants. The concentration of each organic pollutant in the wastewater was 40 mg / L, the catalyst dosage was 0.25 g / L, the wastewater volume was 0.2 L, the temperature was 25°C, the time was 30 min, and the ozone concentration generated by the ozone generator was 20 mg / L, which was introduced into the wastewater at an ozone flow rate of 0.1 L / min.

[0080] Figure 5 The catalyst of Example 1 was demonstrated to exhibit catalytic degradation effects on different organic pollutants. Results showed that the catalyst possessed high catalytic ozone degradation activity for sulfamethoxazole, carbamazepine, and ciprofloxacin, achieving complete degradation of carbamazepine within 6 minutes and complete degradation of sulfamethoxazole and ciprofloxacin within 3 minutes. It also showed good catalytic activity for ibuprofen and phenol.

[0081] Performance Test 6 The stability of the catalyst in Example 1 was verified through multiple cyclic experiments. The catalyst from Example 1 was mixed with wastewater containing ATZ, and a catalytic ozone oxidation reaction was carried out under ozone conditions to degrade ATZ. The concentration of ATZ in the wastewater was 15 mg / L, the catalyst dosage was 0.25 g / L, the wastewater volume was 0.2 L, the temperature was 25℃, the time was 30 min, and the ozone concentration generated by the ozone generator was 20 mg / L, which was introduced into the wastewater at an ozone flow rate of 0.1 L / min.

[0082] Experimental results (such as) Figure 6 The results show that even after five cycles, the ATZ removal efficiency remains at a high level. The ATZ removal rate is 95.4% in the first cycle and 89.9% in the fifth cycle, a decrease of only 5.5%. This indicates that CoFePBA-700 exhibits excellent cycle stability. This performance may be attributed to the effective protection of the cobalt-iron alloy by the carbon coating, preventing the dissolution and aggregation of active components. Simultaneously, the cobalt-iron alloy-carbon interface structure helps maintain the exposure of active sites and the integrity of electron transport channels.

[0083] Performance Test 7 The catalysts from Examples 1 and 3-5 were mixed with ATZ-containing wastewater and subjected to catalytic ozone oxidation under ozone conditions to degrade ATZ. The concentration of ATZ in the wastewater was 15 mg / L, the dosage of each catalyst was 0.25 g / L, the wastewater volume was 0.2 L, the temperature was 25°C, the time was 30 min, and the ozone generator produced an ozone concentration of 20 mg / L, which was introduced into the wastewater at an ozone flow rate of 0.1 L / min.

[0084] The results show that, in comparison, the carbon-coated cobalt-iron alloy catalyst in Example 1 has higher ozone catalytic activity and higher ozone catalytic stability, can rapidly trigger the generation of a large number of highly active oxide species, and exhibits high ATZ removal efficiency.

[0085] As can be understood from the above embodiments, the present invention provides a catalyst for catalytic ozone degradation of recalcitrant organic pollutants in water. In Example 1, the catalyst CoFePBA-700 was used for ozone catalytic water treatment, achieving higher removal and ozone utilization rates at the same ozone dosage, and demonstrating high efficiency and stability for recalcitrant organic pollutants such as atrazine.

[0086] This invention constructs a carbon-coated active metal-iron alloy catalyst through a series of processes including citrate co-precipitation and high-temperature calcination under argon. The carbon coating effectively modulates the electronic structure, promoting the redox reaction of the active metal and iron. This process regulates the adsorption and dissociation of O3 on the catalyst surface, significantly enhancing the O3 catalytic activity of the material, and simultaneously promoting the oxidation-reduction reaction of O2. - / 1 Compared to conventional carbon-coated metal catalysts, the synergistic generation of O2 results in higher O3 utilization, higher removal rate of recalcitrant organic pollutants, better activity retention during recycling, better adaptability to different pH levels, different inorganic ions, and different water matrix interferences, and requires a lower ozone dose to achieve the same removal rate, which helps reduce the risk of byproducts such as bromate.

[0087] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a catalyst for catalytic ozone degradation of organic pollutants, characterized in that, Includes the following steps: S1. Mix the mixed solution of citrate and water-soluble active metal salt with potassium ferricyanide solution to obtain the precursor solution; S2. The precursor solution is allowed to stand at room temperature to form a Prussian blue analogue, thus obtaining the precursor. S3. The precursor is calcined under an argon atmosphere to obtain the catalyst; The water-soluble active metal salt includes at least one of water-soluble cobalt salt or water-soluble nickel salt.

2. The method according to claim 1, characterized in that, The molar ratio of the water-soluble active metal salt to the potassium ferricyanide is 5-7:3-5; and / or, the molar ratio of the water-soluble active metal salt to the citrate is 1:1.3-1.

8.

3. The method according to claim 1, characterized in that, The mixed solution is mixed with the potassium ferricyanide solution by stirring for 2-5 minutes; and / or, the standing time is 20-25 hours.

4. The method according to claim 1, characterized in that, The heating and calcination method includes: heating to 650-750°C at a rate of 3-8°C / min and maintaining the temperature for 2-5 hours.

5. The catalyst prepared by any one of the preparation methods according to claims 1-4, characterized in that, The catalyst has a core-shell structure, wherein the shell is a carbon layer and the core is an active metal-iron alloy, the shell layer covers the surface of the core, and the active metal-iron alloy is a cobalt-iron alloy or a nickel-iron alloy.

6. The catalyst according to claim 5, characterized in that, The shell layer has a thickness of 2-20 nm, and the core has a diameter of 100-300 nm; and / or, the catalyst contains 25%-30% iron and 35%-40% active metal; and / or, the catalyst contains iron in zero, divalent, and trivalent valence states, and cobalt in zero, divalent, and trivalent valence states.

7. A method for ozone degradation of organic pollutants in water, characterized in that, Includes the following steps: Add the catalyst described in any one of claims 5 to 6 to the water to be treated, and introduce ozone to carry out an oxidation reaction.

8. The ozone degradation method according to claim 7, characterized in that, The catalyst is added at a rate of 0.1-1 g / L.

9. The ozone degradation method according to claim 7, characterized in that, The concentration of ozone introduced is 10-30 mg / L, the flow rate of ozone introduced is 0.1-0.5 L / min; and / or, the temperature of the oxidation reaction is 25°C and the time is 10-60 min.

10. The ozone degradation method according to claim 7, characterized in that, The organic pollutants include at least one of atrazine, ibuprofen, ciprofloxacin, sulfamethoxazole, carbamazepine, or phenol.